Coordinating Proliferation, Polarity, and Cell Fate in the Drosophila Female Germline - Hinnant, Taylor D.; Merkle, Julie A.; Ables, Elizabeth T. (Frontiers in Cell and Developmental Biology, 2020)
Gametes are highly specialized cell types produced by a complex differentiation process. Production of viable oocytes requires a series of precise and coordinated molecular events. Early in their development, germ cells are an interconnected group of mitotically dividing cells. Key regulatory events lead to the specification of mature oocytes and initiate a switch to the meiotic cell cycle program. Though the chromosomal events of meiosis have been extensively studied, it is unclear how other aspects of oocyte specification are temporally coordinated. The fruit fly, Drosophila melanogaster, has long been at the forefront as a model system for genetics and cell biology research. The adult Drosophila ovary continuously produces germ cells throughout the organism’s lifetime, and many of the cellular processes that occur to establish oocyte fate are conserved with mammalian gamete development. Here, we review recent discoveries from Drosophila that advance our understanding of how early germ cells balance mitotic exit with meiotic initiation. We discuss cell cycle control and establishment of cell polarity as major themes in oocyte specification. We also highlight a germline-specific organelle, the fusome, as integral to the coordination of cell division, cell polarity, and cell fate in ovarian germ cells. Finally, we discuss how the molecular controls of the cell cycle might be integrated with cell polarity and cell fate to maintain oocyte production.